2020
DOI: 10.1097/md.0000000000021422
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of Chinese herbal medicine and acupuncture for the prevention of mental disorders in interstitial cystitis patients

Abstract: Traditional Chinese medicine (TCM) is commonly used for urinary symptoms in Eastern countries. Since there are few effective treatments available for patients with interstitial cystitis/bladder pain syndrome (IC/BPS), the psychological burden leads to increased healthcare-seeking behavior. Some patients may therefore seek TCM treatment for related urinary symptoms. Due to limited clinical research evaluating the effects of TCM on IC/BPS, we conducted a nationwide population-based cohort study to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 31 publications
(30 reference statements)
0
4
0
1
Order By: Relevance
“…In this study, it was observed that the majority of patients used complementary therapy. Patients with interstitial cystitis often experience a reduced health-related quality of life associated with physical limitations, reduced vitality, increased sleep dysfunction, more pain and more problems with sexual/social functioning (21). Complementary and alternative medicine treatment options for interstitial cystitis are many and should be individualized for each patient (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, it was observed that the majority of patients used complementary therapy. Patients with interstitial cystitis often experience a reduced health-related quality of life associated with physical limitations, reduced vitality, increased sleep dysfunction, more pain and more problems with sexual/social functioning (21). Complementary and alternative medicine treatment options for interstitial cystitis are many and should be individualized for each patient (22).…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggested that this may be due to the fact that herbal products are obtained naturally and they are easily accessible. Due to the paucity of data evaluating the efficacy of treatment approaches and inadequate understanding of the etiology of interstitial cystitis, no single approach is useful for all patients (21). Therefore, it is important to inform patients about the lack of robust evidence for complementary therapies (27).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, in Western countries, CAM has become increasingly popular over the last few decades ( Rakel, 2018 ; Borse et al, 2019 ). The health-seeking behavior studies from various parts of the world suggest widespread use of TCAM for the management of non-communicable diseases ( Gordon et al, 2019 ; Hung et al, 2020 ; Toukabri et al, 2020 ). The pattern is almost similar in both developed and developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with mental disorder frequently have a lower health‐related quality of life, which is linked to physical restrictions, decreased vitality, higher sleep dysfunction, increased pain, and increased sexual/social dysfunction issues. In recent years, mental health has received much interest, especially in developed countries (Hung, Chen, Chen, Chiu, & Chen, 2020). The management of mental problems is carried out in a gradual manner, with the use of therapeutic methods such as behavioral therapy and chemical oral medications.…”
Section: Introductionmentioning
confidence: 99%